Symptomatic hypoglycemia in a nondiabetic adult female recovering from mild COVID‐19 infection: A case report. Issue 11 (12th November 2022) - Grover, Jayant; Verma, Vishesh; Menon, Anil; Dorji, Thinley
Abstract: A 38‐year‐old lady, recently recovered from SARS‐CoV‐2 infection and taking grape seed extract, suffered multiple episodes of severe postprandial hyperinsulinemic hypoglycemia. A careful evaluation ruled out the common etiologies of hypoglycemia and identified grape seed extract consumption as a possible cause. She recovered after stopping the nutritional supplements. In her, hypoglycemia could have resulted from transient beta cell dysfunction associated with SARS‐CoV‐2 infection or proanthocyanidins in the grape seed extract.